Ethanol combined with energy drinks: Two decades of research in rodents - Petribu, Beatriz Nunes; Abrahao, Karina Possa; Souza-Formigoni, Maria Lucia Oliveira (Frontiers in Behavioral Neuroscience, 2023)
Many studies have raised concerns on alcoholic beverages consumption mixed with energy drinks (AmED), which can induce higher rates of binge drinking and earlier development of alcohol dependence. After 20 years of research, few studies with animals focused on the behavioral effects and neurobiological and pharmacological mechanisms underlying this mixture. Sixteen articles were found about AmED effects on rodents which have evaluated voluntary consumption, locomotion, anxiety-like behavior, memory, influence on seizures, biochemical and neurochemical measures. Some of these studies indicated energy drinks (ED) can alter the pattern of use and motivation to consume ethanol (EtOH); increase the expression of sensitization to ethanol stimulant effect and the proportion of sensitized mice; decrease the aversiveness of high concentrations of ethanol, among other effects. AmED also affects ethanol tolerance and its effects on memory are controversial. Data on biochemical and neurochemical parameters after AmED are not consistent, although some effects were observed on blood ethanol concentration, glucose levels, biomarkers for kidney damage, inflammatory response and oxidative stress. These controversial results show that AmED diverse effects may depend on several variables including sex, age and lineage of the animals, duration of the treatment and route of administration. Further research is necessary to evaluate the mechanisms underlying these differences among studies.